Targeting Microglial Population Dynamics in Alzheimer’s Disease: Are We Ready for a Potential Impact on Immune Function? - Martin-Estebane, Maria; Gomez-Nicola, Diego (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s disease (AD) is the most common form of dementia, affecting two-thirds of people with dementia in the world. To date, no disease-modifying treatments are available to stop or delay the progression of AD. This chronic neurodegenerative disease is dominated by a strong innate immune response, whereby microglia plays a central role as the main resident macrophage of the brain. Recent genome-wide association studies (GWASs) have identified single-nucleotide polymorphisms (SNPs) located in microglial genes and associated with a delayed onset of AD, highlighting the important role of these cells on the onset and/or progression of the disease. These findings have increased the interest in targeting microglia-associated neuroinflammation as a potentially disease-modifying therapeutic approach for AD. In this review we provide an overview on the contribution of microglia to the pathophysiology of AD, focusing on the main regulatory pathways controlling microglial population dynamics during the neuroinflammatory response, such as the colony-stimulating factor 1 receptor (CSF1R), its ligands (the colony-stimulating factor 1 and interleukin 34) and the transcription factor PU.1. We also discuss the current therapeutic strategies targeting proliferation to modulate microglia-associated neuroinflammation and their potential impact on peripheral immune cell populations in the short and long-term. Understanding the effects of immunomodulatory approaches on microglia and other immune cell types might be critical for developing specific, effective, and safe therapies for neurodegenerative diseases.